1987
DOI: 10.1080/00021369.1987.10868109
|View full text |Cite
|
Sign up to set email alerts
|

Role of Individual Milk Salt Constituents in Cross-linking by Colloidal Calcium Phosphate in Artificial Casein Micelles

Abstract: Artificial casein micelles were prepared at a casein concentration of 2.5% with various salt compositions, and the content of the casein aggregates cross-linked by colloidal calcium phosphate (CCP) was determined by high-performance gel chromatography on a TSK-GEL G4000SW column, using 6 M urea-simulated milk ultrafiltrate as the effluent. When phosphate was incorporated into calcium caseinate micelle systems, the casein aggregates cross-linked by CCP appeared. In these micelle systems, not all of the formed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
1
3
0
Order By: Relevance
“…This hypothesis was reinforced by the fact that part of the Ca (2 niM) is easily exchangeable (Yamauchi et al 1969;Pierre et al 1983). Furthermore, these results support the work of Aoki et al (1986Aoki et al ( , 1987a, which suggested that the casein-mineral crosslinking occurred as a function of the number of SerP residues present in casein sequences in the order a s2 -CN > a sl -CN > /?-CN. However, in our work we found only a small proportion of phosphopeptides derived from <x s2 -CN, probably because this protein is present in smaller amounts than a sl -CN and /5-CN and is therefore more difficult to detect.…”
Section: Discussionsupporting
confidence: 86%
“…This hypothesis was reinforced by the fact that part of the Ca (2 niM) is easily exchangeable (Yamauchi et al 1969;Pierre et al 1983). Furthermore, these results support the work of Aoki et al (1986Aoki et al ( , 1987a, which suggested that the casein-mineral crosslinking occurred as a function of the number of SerP residues present in casein sequences in the order a s2 -CN > a sl -CN > /?-CN. However, in our work we found only a small proportion of phosphopeptides derived from <x s2 -CN, probably because this protein is present in smaller amounts than a sl -CN and /5-CN and is therefore more difficult to detect.…”
Section: Discussionsupporting
confidence: 86%
“…Whereas soluble Ca levels were significantly lower in the UHT-treated than in the retorted MCC, no difference was observed between the soluble Mg levels between the 2 treatments. It has been shown before that calcium phosphate can form cross-links in artificial casein micelle systems, whereas magnesium phosphate does not have this cross-linking ability (Kaminogawa et al, 1977;Aoki et al, 1987). Thus, it is reasonable to hypothesize that some of the calcium phosphate may have participated in the cross-linking and subsequent aggregation of casein micelles during the UHT treatment, which prevented it from returning into the soluble phase.…”
Section: Discussionmentioning
confidence: 98%
“…It has been proved that caseins are cross-linked through their ester phosphate groups by CCP (Aoki et al 19876). The role of the individual milk salt constituents in crosslinking by CCP has also been examined (Aoki et al 1987a).…”
mentioning
confidence: 99%